The Impact of Monetary Policy on Foreign Direct Investment Flows to Egypt - El-Kharboutly, Maged (The Arab Journal of Administration, 2020)
All countries compete to increase their share of international capital flows although direct foreign investment is of particular importance to developing countries and emerging economies, including Egypt, for its contribution to improving economic growth rates, increasing employment opportunities, reducing the burden on the state budget and bridging the financing gap. In addition to the positive effects of addressing the structural imbalance of the economies of developing countries, as well as contributing to raising the efficiency of human resources through the transfer of technology, and creating an atmosphere of competition for modernization and development, and may also contribute to reducing inflation by satisfying the demand The study aims at explaining the impact of monetary policy on the development of foreign direct investment flows to Egypt through the transmission channels of monetary policy, the most important of which are the interest rate, exchange rate and the impact of the most important monetary indicators, including the size of external debt. We also aim to identify the degree of exchange effect of foreign direct investment and monetary variables. The study showed that there was a negative correlation between the rate of inflation and the inflows of FDI during the study period. The results of the “Granger” causality test also showed the effect of FDI inflows on reducing inflation. On the other hand, flows may limit the government’s ability to control inflation, especially if the central bank uses interest rates to reduce inflation. The central bank must maintain the inflation rate target, taking into account the independence of monetary policy and control the growth rates of money supply and absorption of surplus domestic liquidity associated with capital flows to neutralize its impact in line with the target economic growth rates and avoid generating Inflationary pressures The results also indicate a positive relationship between the exchange rate and flows of foreign direct investment, which is consistent with the economic theory, but a weak signal, in addition to proving a reciprocal relationship, where flows of foreign direct investment affect the exchange rate. Exchange rate to adopt precautionary policies and measures to harmonize maintaining exchange rate stability on the one hand, avoiding speculative risks and overheating of economic activity on the other. FDI flows must be managed through the use of appropriate macroeconomic and structural economic policies. In addition to seeking a degree of integration between the structure of foreign direct investment and the structure of domestic investment and encourage foreign investment accompanied by modern technology and advanced management. Moreover, it is imperative that the state accurately identify the economic sectors that need to increase foreign capital, which adds to the economic wealth and our capabilities to enhance export capacity. Thus, the aim should be to take advantage of foreign direct investment to the extent that it allows the development of the domestic market and prepare it to compete alongside the protection of the domestic industry.